Differences in occupational mortality from pleural cancer, peritoneal cancer, and asbestosis. Issue 11 (November 1995) - Coggon, D; Inskip, H; Winter, P; Pannett, B
Abstract : OBJECTIVE–To assess whether the increased risk of disease related to asbestos in occupations from the construction and engineering industries applies equally to pleural cancer, peritoneal cancer, and asbestosis. METHODS–Analysis was based on deaths among men aged 20-74 in England and Wales during 1979-80 and 1982-90. (n = 1, 656, 096). Information about cause of death and the last full time occupation of decedents was derived from death certificates. Proportional mortality ratios (PMRs) by occupation were calculated for each of pleural cancer, peritoneal cancer, and asbestosis. RESULTS–Altogether, 2848 deaths were attributed to cancer of the pleura, 362 to cancer of the peritoneum, and 281 to asbestosis. When occupations were ranked according to PMRs from these diseases, striking differences were found. The category of construction workers which included laggers had the highest mortality from peritoneal cancer (PMR 990, 64 deaths), but a PMR of only 160 (77 deaths) for pleural cancer. In contrast, several occupations with much higher mortality from pleural tumours had no excess of peritoneal cancer. PMRs for asbestosis related more closely to those for peritoneal than pleural cancer. CONCLUSIONS–These findings suggest that the exposure-response relations for diseases related to asbestos are not all linear, and that risks of pleural mesothelioma may be underestimated by simple extrapolation from observations in cohorts with heavy exposure.